2016
DOI: 10.13160/ricns.2016.9.1.72
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening and Biological Studies of Boerhavia Diffusa Linn

Abstract: Hexane, ethyl acetate and methanol extracts of whole plant of Boerhavia diffusa were screened for phytochemical and biological activities. Qualitative phytochemical screening via colorimetric method and the quantitative estimation of phenolic and flavonoid content were performed. Antioxidant assay using DPPH scavenging method was studied. Antimicrobial screening of plant extracts was done by cup diffusion technique. Cytotoxic activity of B. diffusa was studied by brine shrimp bioassay and anthelminthic activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The only appearance of phytosterols was seen in ethyl acetate extract, and all other constituents, that is, alkaloids, carbohydrates, saponins, flavonoids, and glycosides, are absent. The study was further corroborated by a literature search [33–37] that revealed the root part of the plant is rich in flavonoids and rotenoids (isoflavonoids) and considering its weak and moderately polar nature, mainly they get isolated in petroleum ether and ethyl acetate solvents. The results of various tests performed for various phytoconstituents are listed in Table 1.…”
Section: Resultsmentioning
confidence: 59%
“…The only appearance of phytosterols was seen in ethyl acetate extract, and all other constituents, that is, alkaloids, carbohydrates, saponins, flavonoids, and glycosides, are absent. The study was further corroborated by a literature search [33–37] that revealed the root part of the plant is rich in flavonoids and rotenoids (isoflavonoids) and considering its weak and moderately polar nature, mainly they get isolated in petroleum ether and ethyl acetate solvents. The results of various tests performed for various phytoconstituents are listed in Table 1.…”
Section: Resultsmentioning
confidence: 59%
“…The result indicates that the extract is moderately cytotoxic and hence connotes the presence of bioactive compounds (Suryawanshi et al, 2020). It also showed a higher cytotoxicity index compared to the LC50 (165.19 μg/mL) value for the methanolic extract of B. diffusa which is a specie in the genus (Gautam et al, 2016). Similarly Khalid et al (2011) also reported LC50 value of the n-hexane extract of B. diffusa as 140.55 μg/mL.…”
Section: Cytotoxic Assay Of B Adscendensmentioning
confidence: 86%
“…The median lethal concentration (LC50) was determined graphically. This represents the concentration that produced death in half of larvae population after 18-24 hr exposure (Gautam et al, 2016).…”
Section: Brine Shrimp Testmentioning
confidence: 99%